2009
DOI: 10.1080/10508410802597390
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Offs in Synthetic Vision System Display Resolution, Field of Regard, Terrain Data Density, Texture, and Shading During Off-Path Operations

Abstract: We conducted 2 independent fixed-base flight simulator studies to determine tradeoffs in synthetic vision system (SVS) display resolution, field of regard, terrain data density, texture, and shading during off-path operations. The data we present herein are a synthesis of prior work and may be useful for consideration by SVS designers and certification entities. Pilots flew off-path tasks, following the middle of a curved valley depicted on the SVS. The SVS parameters were manipulated between runs and cross-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…That is, a perspective view is biased due to perspective distortions, causing pilots to make judgment errors regarding the relative location, height, and ultimately the avoidance of terrain obstacles [3,5]. To mitigate these issues, the SVS community has explored solutions such as terrain coloring to indicate high-elevated areas, using high-resolution textures to increase speed perception and judgment of distances [6], and optimal field-of-view settings to reduce spatial biases [4,6].…”
mentioning
confidence: 99%
“…That is, a perspective view is biased due to perspective distortions, causing pilots to make judgment errors regarding the relative location, height, and ultimately the avoidance of terrain obstacles [3,5]. To mitigate these issues, the SVS community has explored solutions such as terrain coloring to indicate high-elevated areas, using high-resolution textures to increase speed perception and judgment of distances [6], and optimal field-of-view settings to reduce spatial biases [4,6].…”
mentioning
confidence: 99%
“…As we discussed in the introduction, there are other properties of perspective displays that can impact compression rates. These include display size, display resolution, other GFOVs, as well as different displayed trajectories and camera orientations [8,9,22,[26][27][28][29]. Given that the results presented here suggest that compression rates can be used to explain judgment biases that manifest for both between-and within-display differences, they should be able to explain the biases seen in all of these studies.…”
Section: E Other Display Considerationsmentioning
confidence: 94%
“…There were seven textures used in the experiment and two GFOVs (30 • and 60 • ). It is important to note that different terrain textures can contain different depth cues and can thus have a significant impact on the perception of spatial quantities [18,22]. However, the purpose of the work presented here was to investigate the impact of compression rates on human spatial judgments.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…NASA and others have developed and shown that SVS technologies provide significant improvements in terrain awareness and reductions for the potential of Controlled-Flight-Into-Terrain incidents/accidents, 3,4 improvements in flight technical error to meet Required Navigation Performance criteria, [7][8][9] and improvements in situation awareness without increased workload compared to current generation cockpit technologies. [10][11][12] As such, SVS, often displayed on a head-down display (HDD), is emerging as standard equipage for Part 23 and Part 25 flight decks even though, to date, no operational credit is obtained from equipage.…”
Section: Introductionmentioning
confidence: 99%